Ketogenic Diet Therapy for Drug-Resistant Epilepsy and Cognitive Impairment in Children With Tuberous Sclerosis Complex - Fang, Yu; Li, Dan; Wang, Man; Zhao, Xia; Duan, Jing; Gu, Qiang; Li, Baomin; Zha, Jian; Mei, Daoqi; Bian, Guangbo; Zhang, Man; Zhang, Huiting; et al. (Frontiers in Neurology, 2022)
Objective Tuberous sclerosis complex (TSC) is a rare disease with a high risk of epilepsy and cognitive impairment in children. Ketogenic diet (KD) therapy has been consistently reported to be beneficial to TSC patients. In this study, we aimed to investigate the efficacy and safety of KD in the treatment of drug-resistant epilepsy and cognitive impairment in children with TSC. Methods In this multicenter study, 53 children (33 males and 20 females) with drug-resistant epilepsy or cognitive impairment caused by TSC were retrospectively recruited from 10 hospitals from January 1, 2010, to December 31, 2020. Intention-to-treat analysis was used to evaluate seizure reduction and cognition improvement as outcomes after KD therapy. Results Of the 53 TSC patients included, 51 failed to be seizure-free with an average of 5.0 (range, 4–6) different anti-seizure medications (ASMs), before KD therapy. Although the other two patients achieved seizure freedom before KD, they still showed psychomotor development delay and electroencephalogram (EEG) abnormalities. At 1, 3, 6, and 12 months after the KD therapy, 51 (100%), 46 (90.2%), 35 (68.6%), and 16 patients (31.4%) remained on the diet therapy, respectively. At these time points, there were 26 (51.0%), 24 (47.1%), 22 (43.1%) and 13 patients (25.5%) having ≥50% reductions in seizure, including 11 (21.6%), 12 (23.5%), 9 (17.6%) and 3 patients (5.9%) achieving seizure freedom. In addition, of 51 patients with psychomotor retardation, 36 (36 of 51, 70.6%) showed cognitive and behavioral improvements. During the KD therapy, no serious side effects occurred in any patient. The most common side effects were gastrointestinal disturbance (20 of 53, 37.7%) and hyperlipidemia (6 of 53, 11.3%). The side effects were gradually relieved after adjustment of the ketogenic ratio and symptomatic treatment. Conclusion KD is an effective and safe treatment for TSC-related drug-resistant epilepsy and cognitive impairment in children. KD can reduce seizure frequency and may potentially improve cognition and behavior.